The impact of holding stressors on the immune function and haemolymph biochemistry of Southern Rock Lobsters (Jasus edwardsii). Issue 89 (June 2019) - Day, Ryan D.; Fitzgibbon, Quinn P.; Gardner, Caleb
Abstract: Lobsters are fished world-wide due to their status as a high value, luxury seafood. A large proportion of the product is sold via live export, with lobsters subject to a range of stressors during holding post-capture. Improving the current understanding of the immune response to these stressors assists in improving efficiency and reducing loss in the chain between capture and consumption. In this study, the immune status of four treatment groups of Southern Rock Lobster ( Jasus edwardsii ) were studied: controls recently landed from a fishing boat, lobsters displaying advanced shell necrosis, lobsters in an unexplained moribund state and lobsters held in a processing facility for 10 weeks in standard conditions (i.e. high density, fasted). A total of 15 immune parameters and 19 haemolymph biochemical parameters were assayed. Phenoloxidase activity was only sporadically observed in haemocyte lysate and was consistently observed at a low level in the plasma with no difference between treatments for either. Haemocyte lysate prophenoloxidase activity was detected in most individuals, with no differences found between treatments. Prophenoloxidase in the plasma showed the highest level of activity, with the shell necrosis treatment demonstrating an elevated activity level relative to the other three treatments. Cell viability was not affected in any treatment. Lobsters with shell necrosis had a reduced capacity for phagocytosis, a significantly higher total haemocyte count, fewer hyalinocytes and more granulocytes and semigranulocytes. Fasted lobsters showed an opposite shift, with significantly more hyalinocytes compared to the other treatments and very few granulocytes and semigranulocytes. The balance of a range electrolytes, minerals metabolites and enzymes were affected in shell necrosis and fasted treatments, raising them as potential markers for immunocompromised lobsters. Multivariate analysis of all assayed parameters showed that all individuals in the necrosis treatment showed a similar, distinct immune response and that the fasted treatment, along with one control and one moribund individual, showed a separate intermediate response. The remainder of the control and moribund lobsters demonstrated a distinct "non-response" in comparison. These results offer a characterisation of the physiological response to common challenges during post-capture holding of rock lobsters, demonstrating the differential response to pathogenic bacterial infection, long term fasting, non-specific moribundity and the stress of capture and transport. Highlights: The haemolymph of Southern Rock Lobsters was analysed, comparing 15 immune response parameters and 19 biochemistry parameters. Treatments clustered into two distinct categories, "response" or "non-response". Lobsters with shell necrosis and fasted lobsters demonstrated two distinct types of response. Control lobsters and some lobsters suffering an unexplained moribundity demonstrated non-response. Activity of the phenoloxidase system was mainly comprised of prophenoloxidase and was observed primarily in the plasma. Haemocyte cell populations and immune function shifted in response to treatments.